Meramal Kualiti Air Sungai Menggunakan Kaedah Analisis Diskriminan Dua Kumpulan Berdasarkan Komposisi Alga - Wan Obeng, Sharifah Nasriah (Universiti Sains Malaysia, 2006)
Algae are large and diverse group of aquatic plantlike organisms. The algae contain chlorophyll and can manufacture their own food through the process of photosynthesis. They are distributed worldwide throughout the sea, freshwaters, rivers and wetland. The existences of the alga composition have a greater influence to the river’s water in Malaysia. There are several traditional approaches used a long time ago in predicting the river’s water quality but it is time consuming to classify whether the water is clean or polluted. So, we need a smarter way to predict the quality of river’s water accurately and easily based on the alga composition. In this project, the two group discriminant analysis is used to predict the river’s water quality. The results show that the proposed system classifies the river’s water with 94.9% of accuracy. The results obtained prove that the discriminant analysis is suitable and has high capability to be used as intelligent classifier to classify the river’s water quality based on algae composition. As a conclusion, the two group discriminant analysis is one of the smarter ways to predict the quality of the river’s water whether it is clean or polluted accurately based on the alga composition.